Sound absorption coefficient in situ: An alternative for estimating soil loss factors - Freire, Rosane [UNESP]; Meletti de Abreu, Marco Henrique; Okada, Rafael Yuri [UNESP]; Soares, Paulo Fernando; GranhenTavares, Celia Regina (Elsevier B.V., 2015)
The relationship between the sound absorption coefficient and factors of the Universal Soil Loss Equation (USLE) was determined in a section of the Maringa Stream basin, Parana State, by using erosion plots. In the field, four erosion plots were built on a reduced scale, with dimensions of 2.0 x 12.5 m. With respect to plot coverage, one was kept with bare soil and the others contained forage grass (Brachiaria), corn and wheat crops, respectively. Planting was performed without any type of conservation practice in an area with a 9% slope. A sedimentation tank was placed at the end of each plot to collect the material transported. For the acoustic system, pink noise was used in the measurement of the proposed monitoring, for collecting information on incident and reflected sound pressure levels. In general, obtained values of soil loss confirmed that 94.3% of material exported to the basin water came from the bare soil plot, 2.8% from the corn plot, 1.8% from the wheat plot, and 1.1% from the forage grass plot. With respect to the acoustic monitoring, results indicated that at 16 kHz erosion plot coverage type had a significant influence on the sound absorption coefficient. High correlation coefficients were found in estimations of the A and C factors of the USLE, confirming that the acoustic technique is feasible for the determination of soil loss directly in the field. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Erosion; Acoustics; Pink noise; Monitoring; Environment